EFEKTIVITAS EKSTRAK KACANG KEDELAI (Glycine max L. Mer) PENGGANTI ZA TERHADAP KUALITAS NATA DE BANANA SKIN SEBAGAI POTENSI RANCANGAN LEMBAR KERJA SISWA DALAM PEMBELAJARAN BIOLOGI DI SMA - Wulandari, Kartika; ', Darmawati; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to know the effectiveness of the extract of soybean (Glycine max L. Mer) in lieu of ZA on the quality of Nata de banana skin and analyze potential design Student Worksheet (LKS) in learning biology in high school of research results. This research consists of two stage. The first stage of research that is making nata de banana skin using the experimental method with completely randomized design (CRD), which consists of 5 treatments and 3 replications. Parameters that observed is measured were thickness, fiber content and organoleptic test. The results of research obtained then analyzed ANOVA and a further test DMRT at 5% level. The second stage is the phase design (draft) Student Worksheet (LKS) sourced from the results of the first stage. The research result show that the soy extract significant effect on the thickness, fiber content and organoleptic tests. The best treatment is the use of soy extract 50%. Which results in the thickness of 0,89cm and crude fiber content of 1.88%. The resulting fiber content has met the quality requirements according to SNI 01-4317-1996 is a maximum of 4.5%. As for organoleptic texture, color, aroma, taste and preference level best against the use of soy extract 50%.The results of this research was be used as design student worksheet (LKS) in subject matter the outcomes of the implications of biotechnology on salingtemas the sub material with conventional biotechnology.